Development of microemulsion containing thai herbal remedy extract for treatment of urticaria - Natta Choedchutirakul; Intouch Sakpakdeejaroen; Sumalee Panthong (Journal of Advanced Pharmaceutical Technology & Research)
Herbal medicine can be used as an alternative treatment to alleviate allergy symptoms in individuals with urticaria. The herbal remedy comprised four plant components, including Allium ascalonicum, Acanthus ilicifolius, Bambusa blumeana, and Rhinacanthus nasutus, in equal amounts. It was administered to impacted areas of the skin affected by allergies. Nevertheless, the disadvantages of herbal products include their limited ability to penetrate the skin. Microemulsion (ME) is a topical medication delivery device that enhances drug absorption into the skin. This work aims to develop and optimize a ME containing an herbal remedy extract. The construction methods utilized were pseudo-ternary phase diagrams and mixture design using system engineering software. Data were calculated and reported as means ± standard. Statistical significance was indicated when P < 0.05. The optimal herbal ME consisted of 4%–5% isopropyl myristate, 35%–45% Smix, and 46%–58% water. The stability studies demonstrated consistent physical properties and a low level of viscosity. The pH, particle size, polydispersity index, and zeta potential readings have remained stable after storage under nine heating and cooling cycles. The ME exhibited sustained release of rhinacanthin-C, with a steady release rate of 10.34% ± 0.03% from 0.5 h to 20.21% ± 0.11% at 8 h. The Kae-Lom-Pid proves to be suited for MEs and can serve as a model for pharmaceutical development.